2013
DOI: 10.1021/nl403252x
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Ligand Spacing Influences Receptor Triggering in T Cells and NK Cells

Abstract: Bioactive nanoscale arrays were constructed to ligate activating cell surface receptors on T cells (the CD3 component of the TCR complex) and NK cells (CD16). These arrays are formed from biofunctionalized gold nanospheres with controlled interparticle spacing in the range 25 – 104 nm. Responses to these nanoarrays were assessed using the extent of membrane-localized phosphotyrosine in T cells stimulated with CD3-binding nanoarrays, and the size of cell contact area for NK cells stimulated with CD16-binding na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 68 publications
10
113
1
Order By: Relevance
“…Therefore, we hypothesize NK signal integration occurs by the relative sizedependent colocalization of receptors at the NK IS, and this is the explanation for the functional differences observed for elongated ligands. Considering the differences observed at a nanometer-scale, our results further support recent evidence that immune cell receptors show a nanometer-scale organization, with functional associated implications [19,22,50,[52][53][54][55]. Interestingly, there is mounting evidence that the molecular mechanisms behind immune inhibition are in part spatially restricted and common to various immune cells such as T, B and NK cells [56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, we hypothesize NK signal integration occurs by the relative sizedependent colocalization of receptors at the NK IS, and this is the explanation for the functional differences observed for elongated ligands. Considering the differences observed at a nanometer-scale, our results further support recent evidence that immune cell receptors show a nanometer-scale organization, with functional associated implications [19,22,50,[52][53][54][55]. Interestingly, there is mounting evidence that the molecular mechanisms behind immune inhibition are in part spatially restricted and common to various immune cells such as T, B and NK cells [56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…The mean interparticle spacing is 48 ± 8 nm (Fig. 1C), which is physiologically optimal for antigen-mediated T-cell adhesion and functional responses (14,15). Each particle presents an average of 4 ± 1 DNA hairpins (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have further highlighted the importance of nanoscale ligand geometry in immune system responses [ 109 , 110 ]. For example, using the block copolymer micelle lithography (BCML) approach, Delcassian et al [ 109 ] generated CD3 and CD16 antibody patterns to monitor the effect of ligand spacing on the activation levels of T cells and Natural Killer (NK) cells. The activations were assessed in terms of membrane-localized phosphotyrosine for T cells and the size of contact area for the NK cells, and the study showed decreased cell response with increasing ligand spacing in both cell types, with the threshold activation at the ligand spacing being 69 nm and 104 nm for T cells and NK cells, respectively.…”
Section: Biomolecular Cuesmentioning
confidence: 99%